Analisis Kompetensi Mahasiswa Program Studi Pendidikan Teknik Elektro pada Praktik Lapangan Kependidikan - Anggraini, Miranti Dwi; Usmeldi, Usmeldi (Jurnal Pendidikan Teknik Elektro, 2025)
This study aims to analyze the competence of students of the Electrical Engineering Education study program in educational field practice, especially in pedagogical and professional aspects. This study uses a quantitative approach with a data collection method in the form of a questionnaire. Before the questionnaire was distributed to students, a trial was conducted to test its validity and reliability. The data obtained from the questionnaire will be measured using a Likert scale of 1-5. The analysis method used is descriptive statistical analysis using the Respondent Achievement Level (RAL). The subjects in this study were 30 students of the Electrical Engineering Education study program class of 2020 who had carried out educational field practice. The results of this study indicate that most students of the Electrical Engineering Education Study Program have sufficient mastery of pedagogical and professional competencies. For this reason, improvements are needed in both competencies, because there are still weaknesses in several indicators.